2010
DOI: 10.2353/ajpath.2010.100446
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of PTGER2 Confers Prostaglandin E2 Resistance in Fibrotic Fibroblasts from Humans and Mice

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating lung disease that is characterized by excessive proliferation of fibroblasts. The lipid mediator prostaglandin E 2 (PGE 2 ) has the capacity to limit fibrosis through its inhibition of numerous functions of these fibroblasts; however, in the setting of fibrosis, fibroblasts have been shown to be resistant to PGE 2 . We have linked such resistance to decreased expression levels of the E prostanoid 2 (EP2) receptor. In this study, in fibroblasts from both mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 46 publications
9
111
0
2
Order By: Relevance
“…Variability in PGE 2 responsiveness is consistent with our previous studies on PGE 2 inhibition of collagen expression and fibroblast proliferation (26). In those studies involving fibroblasts, but not myofibroblasts, we identified several mechanisms that accounted for variable PGE 2 resistance, including decreased expression of EP2 (by DNA hypermethylation [44]) and decreased activation of the downstream signaling molecule, protein kinase A (26). Further studies would be needed to determine the extent and the mechanism(s) of resistance of IPF cells to PGE 2 reversal of myofibroblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…Variability in PGE 2 responsiveness is consistent with our previous studies on PGE 2 inhibition of collagen expression and fibroblast proliferation (26). In those studies involving fibroblasts, but not myofibroblasts, we identified several mechanisms that accounted for variable PGE 2 resistance, including decreased expression of EP2 (by DNA hypermethylation [44]) and decreased activation of the downstream signaling molecule, protein kinase A (26). Further studies would be needed to determine the extent and the mechanism(s) of resistance of IPF cells to PGE 2 reversal of myofibroblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…PGE2 has long been considered an antifibrotic molecule because it inhibits fibroblast proliferation, collagen synthesis, migration, and differentiation to myofibroblasts and induces fibroblasts apoptosis (45)(46)(47). Fibroblasts derived from IPF lungs exhibit a relative deficiency of PGE2 production as well as reduced responsiveness to PGE2 (48)(49)(50). Several studies suggested that bleomycin-induced fibrosis is enhanced when PTGS2-derived PGE2 is low or absent (51-53), whereas others did not observe the effects to the same extent (54) or suggested alternative pathways to PGE2 production (55).…”
Section: Discussionmentioning
confidence: 99%
“…15,24,91,92 However, fibroblasts from both bleomycin-injured and IPF lung become less responsive to this feedback from epithelial cells because promoter hypermethylation reduces expression of a key PGE 2 receptor, EP2. 26,28,93 In addition, myofibroblasts are a major source of plasminogen activator inhibitor 1; plasminogen activator inhibitor 1 inhibits the conversion of plasminogen to plasmin, and plasmin stimulates PGE 2 synthesis by lung epithelial cells. 15,94,95 Thus, the PGE 2 -dependent negative feedback loop may serve as an informative example of how regeneration occurs from a self-limited wound healing response, whereas an imbalance in feedback inhibition…”
Section: Pericytes and Interstitial Fibroblasts In Lung Regenerationmentioning
confidence: 99%